2016
DOI: 10.1371/journal.pone.0156241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Salinity on Sucrose Metabolism in Cotton Leaves

Abstract: This study investigated sucrose metabolism of the youngest fully expanded main-stem leaf (MSL) and the subtending leaf of cotton (Gossypium hirsutum L.) boll (LSCB) of salt-tolerant (CCRI-79) and salt-sensitive (Simian 3) cultivars and its relationship to boll weight under low, medium and high soil salinity stress in Dafeng, China, in 2013 and 2014. The results showed that with increased soil salinity, 1) both the chlorophyll content and net photosynthetic rate (Pn) decreased, while the internal CO2 concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 30 publications
3
25
0
1
Order By: Relevance
“…The reduction in Chl levels and consequent biomass loss were evident in other studies under salt stress, and the possible cause was attributed to the direct effects of accumulated Na + and ROS (Qin et al, 2010; Mostofa et al, 2015). In accordance with other reports, our results also implied that Chl a is more sensitive to salinity than Chl b (Li et al, 2008; Peng et al, 2016). Chl a is the most abundant and integral part of the light-harvesting complex, whereas Chl b as an accessory pigment acts indirectly in photosynthesis by transmitting photons to the Chl a (Chen, 2014; Gururani et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in Chl levels and consequent biomass loss were evident in other studies under salt stress, and the possible cause was attributed to the direct effects of accumulated Na + and ROS (Qin et al, 2010; Mostofa et al, 2015). In accordance with other reports, our results also implied that Chl a is more sensitive to salinity than Chl b (Li et al, 2008; Peng et al, 2016). Chl a is the most abundant and integral part of the light-harvesting complex, whereas Chl b as an accessory pigment acts indirectly in photosynthesis by transmitting photons to the Chl a (Chen, 2014; Gururani et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…In general, we speculate that the garlic-induced sugar accumulation in the leaves might be associated with an increase in the net activity of sucrose-synthetic enzymes (SPS, SS-s). Sucrose synthetase-cleavage (SS-c) decreased markedly, which suggests that salinity-mediated decreases in both might reflect the reducing capacity of assimilates in the source-to-sink translocation, ultimately flagging the sink viability [71]. Phenolic acid also caused the modification of the carbohydrate status.…”
Section: Metabolism Of Carbohydratesmentioning
confidence: 99%
“…Excavating elite alleles that can Cotton yield decreases under salt stress. The previous studies reported that SBW, LP and BNPP remarkably decreased under salt stress [46][47][48]. In present study, we selected four different field soil salt environments with two year replicates to investigate the lint yield components of cotton accessions.…”
Section: Discussionmentioning
confidence: 97%